OPTIMIZATION METHOD FOR CONTROL OF VOLTAGE LEVEL AND ACTIVE POWER LOSSES BASED ON OPTIMAL DISTRIBUTED GENERATION PLACEMENT USING ARTIFICIAL NEURAL NETWORKS AND GENETIC ALGORITHMS - Vukobratović, Marko; Marić, Predrag; Hederić, Željko (Journal of Energy Technology, 2024)
This paper presents a method for reducing active power system losses and voltage level regulation by implementing adequate distributed generation capacity on the appropriate terminal in a distribution system. Active power losses are determined using an Artificial Neural Network (ANN) using simultaneous formulation for the determination process based on voltage level control and injected power. Adequate installed power of distributed generation and the appropriate terminal for distributed generation utilization are selected by means of a genetic algorithm (GA), performed in a distinct manner that fits the type of decision-making assignment. The training data for Artificial Neural Network (ANN) is obtained by means of load flow simulation performed in DIgSILENT PowerFactory software on a part of the Croatian distribution network. The active power losses and voltage conditions are simulated for various operation scenarios in which the back propagation artificial neural network model has beentested to predict the power losses and voltage levels for each system terminal, and GA is used to determine the optimal terminal for distributed generation placement.
Keywords: distributed generation; Artificial Neural Network; Genetic Algorithm; voltage control